Electroconvulsive Therapy in Italy—Current Dissemination of Treatment and Determining Factors of the Past. Issue 4 (December 2020) - Wilhelmy, Saskia; Grözinger, Michael; Groß, Dominik; Conca, Andreas
Abstract : Objectives: The history of electroconvulsive therapy (ECT) spans eight decades, over which period this method of treatment has been modernized. At the same time, however, the conflict between acceptance and rejection of ECT therapy remains unresolved today. This ambivalence is particularly noticeable in Italy, where the number of uses of ECT has been declining for several years. The aim of the present study is to examine the distribution and use of ECT in Italy today in comparison to 2009 and to analyze the factors that have influenced this downward development. Methods: A cross-sectional study using a standardized Italian-language questionnaire was conducted in 2017 to investigate the dissemination and practice of ECT in Italy. The study was addressed to all public and private hospitals providing ECT as a treatment. Results: Of the 145 mental health facilities in Italy, only 9 offered ECT. A total of 293 patients were treated with ECT within 1 year (mainly for depression). Rates for 3-year treatments in the centers yielded an uneven picture: 4 centers showed an increase in cases and just as many a decline. A north-south divide existed in terms of geographical distribution: centers were mainly located in the north in 2017. Conclusions: The study shows that the dissemination and use of ECT have reached a historical low in Italy. It further documents the extent to which the use of ECT declined after 2009. Three factors that have accompanied this development are discussed. If this downward trend is to be reversed, it will be necessary to develop a new approach so as to engender a perception of ECT as a viable treatment option.